KDM6B promotes ovarian cancer cell migration and invasion by induced transforming growth factor‐β1 expression. Issue 1 (11th September 2018) - Liang, Shumei; Yao, Qingmin; Wei, Deying; Liu, Ming; Geng, Feng; Wang, Qin; Wang, Yun‐shan
Abstract: KDM6B, also known as JMJD3, is a member of the family of histone lysine demethylase (KDMs), which is closely related to many types of cancers. However, its role and the underlying mechanisms in ovarian cancer remain unknown. Here we show that KDM6B is elevated in epithelial ovarian cancer and its expression level is closely related with metastasis and invasion. In addition, survival analysis showed that high expression of KDM6B was associated with low overall survival in ovarian cancer patients. Overexpression of KDM6B in epithelial ovarian cancer cells promoted proliferation, epithelial‐mesenchymal transition (EMT), migration and invasion in vitro, and enhanced metastatic capacities in vivo. On the contrary, silencing KDM6B in invasive and metastatic ovarian cancer cells inhibited these processes. Mechanistically, we found that KDM6B exerts its function by modulating the transforming growth factor‐β1 (TGF‐β1) expression, and TGF‐β1 signal pathway inhibitor LY2157299 significantly inhibited KDM6B‐induced proliferation, migration, metastasis, and EMT in ovarian cancer cells. Our findings, for the first time, reveal the pivotal role of KDM6B in the invasion and metastatic behavior of epithelial ovarian cancer. Thus, targeting KDM6B may be a useful strategy to interfere with these behaviors of epithelial ovarian cancer. Abstract : Our findings, for the first time, reveal the pivotal role of KDM6B in the invasion and metastatic behavior of epithelial ovarian cancer. Thus, targeting KDM6B may be a useful strategy to interfere with these behaviors of epithelial ovarian cancer.